Colombia Between Neoliberal Peace and Democratic Peace - de Sousa Santos, Boaventura (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
As I write this (January 2017) the Colombian peace process enters its implementation period after the new version of the agreement between the government and the FARC (Revolutionary Armed Forces of Colombia) has been ratified by the Colombian Congress. Peace negotiations between the government and the ELN(National Liberation Army) have also begun. This is a time of opportunities and blockades, of aspirations and frustrations, a time of hope though also of fear. In this paper I will offer some brief reflections on the relationship between democracy and peace as well as on the way how post-agreement developments can contribute towards the democratization of Colombian society